Where is Value in Digital Higher Education: From Commodities to Assets - Komljenovic, Janja (International Higher Education, 2022)
Students, academics, and higher education institutions’ administrators and leaders use digital platforms in their everyday work. A diversity of platforms offer various services, target different clients, and include different business models. Most of these platforms are proprietary and form the edtech industry. We should pay attention to the specific economic form of coordination in which digitalization of and in higher education is expanding, namely assetization.